Recent advancement of hybrid materials used in chemical enhanced oil recovery (CEOR): A review - Hamza, M.F. (Institute of Physics Publishing, 2017)
Depletion of natural oil reserves has forced oil industries to focus on tertiary recovery methods to extract residual oil after exhausting the primary and secondary methods. Among the Enhance Oil Recovery (EOR) technologies, Chemical EOR (CEOR) is gaining popularity. Despite research efforts to increase the recovery using CEOR, increasing complexity in extraction methods are encountered. With changes in reservoir conditions (high temperature, pressure and salinity) and crude oil properties, existing chemicals used in CEOR, such as alkali, polymers and surfactants do not function desirably. These conditions have detrimental effects on the performance of EOR chemicals, like precipitation, degradation, etc. Development and utilization of effective EOR hybrids such as surfactant-polymer, polymer-nanomaterial, surfactant-nanomaterial and polymer-surfactant-nanomaterial had prevailed the effects of harsh reservoir conditions, and their applications in oil fields in recent years have increased the success of EOR. The synergistic effects between the hybrid components play major roles in improving the properties that could withstand the effect of extreme reservoir conditions and changes in crude oil properties. Therefore, this paper is aimed at reviewing recent advances in CEOR hybrid technologies, and discusses the basic concept, applications, advancement and limitations of different hybrid materials used in CEOR processes. © Published under licence by IOP Publishing Ltd.